Análisis del uso de la red social facebook del diario El Universo y su impacto en los usuarios entre 18 y 65 años de la ciudad de Guayaquil en la parroquia Pedro Carbo - Bravo Morán, Andreina Teresa (2018)
The main objective of this research project is to analyze the use of the social network Facebook of Diario El Universo and its impact on users. In order to obtain all the necessary data, an analysis of the various areas covered by the topic was carried out, historical and theoretical references were used, starting from the beginnings of the written press and its technological processes both in machinery and the source used to spread the news. The approach used was mixed (quantitative - qualitative). Surveys were conducted to 253 readers of the newspaper El Universo, in the Pedro Carbo parish through a simple random sampling with an age range from 18 years to 65 years old. The questions asked were based on consumption, user interaction and qualification of the publications in Facebook of the newspaper El Universo……